Weed management and fertilization limit the potential of cassava productivity in subtropical environment - Cardoso, Paula de Souza; Alves, Alexandre Ferigolo; Friedrich, Eduardo Daniel; Tironi, Luana Fernandes; Ulguim, André da Rosa; Streck, Nereu Augusto; Zanon, Alencar Junior (Revista de Ciências Agroveterinárias, 2022)
The objectives of this study were to evaluate the response to fertilization and different weed control periods in the accumulation of dry matter of cassava leaves, stems, roots, and fresh mass roots yield. Two experiments were carried out on commercial fields in Ibarama, and Santa Maria municipalities located at the Rio Grande do Sul State, South Brazil, during the 2018/2019 growing season. Five treatments, varying chemical fertilizer applications and herbicides were used to represent management practices commonly used by farmers in Southern Brazil. The Simanihot process-based model simulated cassava growth, development, and productivity under potential conditions. Results show that the recommended dose of fertilizers and liming combined with pre-emergent herbicide and three mechanical weed clear management showed a 72% increase in root productivity compared to the management used by the average yield of smallholder farmers. Therefore, it is possible to reach 80% of the potential productivity by keeping the cassava crop free from weed interference and applying fertilizers. The presence of weeds during the first 100 days after planting reduced about 50% of the plant dry matter production in Ibarama and Santa Maria. Interestingly, it also affects 79.2% of fresh roots productivity in Ibarama. The objectives of this study were to evaluate the response to fertilization and different weed control periods in the accumulation of dry matter of cassava leaves, stems, roots, and fresh mass roots yield. Two experiments were carried out on commercial fields in Ibarama, and Santa Maria municipalities located at the Rio Grande do Sul State, South Brazil, during the 2018/2019 growing season. Five treatments, varying chemical fertilizer applications and herbicides were used to represent management practices commonly used by farmers in Southern Brazil. The Simanihot process-based model simulated cassava growth, development, and productivity under potential conditions. Results show that the recommended dose of fertilizers and liming combined with pre-emergent herbicide and three mechanical weed clear management showed a 72% increase in root productivity compared to the management used by the average yield of smallholder farmers. Therefore, it is possible to reach 80% of the potential productivity by keeping the cassava crop free from weed interference and applying fertilizers. The presence of weeds during the first 100 days after planting reduced about 50% of the plant dry matter production in Ibarama and Santa Maria. Interestingly, it also affects 79.2% of fresh roots productivity in Ibarama.